Further Characterization of SMC1A Loss of Function Epilepsy Distinct From Cornelia de Lange Syndrome. (April 2022) - Barañano, Kristin W.; Kimball, Amy; Fong, Susan L.; Egense, Alena S.; Hudon, Catherine; Kline, Antonie D.
Cornelia de Lange syndrome is a rare developmental malformation syndrome characterized by small stature, limb anomalies, distinctive facial features, developmental delays, and behavioral issues. The diagnosis of Cornelia de Lange syndrome is made clinically or on the basis of an identified variant in one of the genes associated with Cornelia de Lange syndrome. SMC1A variants are the cause of 5% of the cases of Cornelia de Lange syndrome. SMC1A is located on the X-chromosome and is thought to escape X-inactivation in some females. Patients with SMC1A variants are being increasingly identified through panel testing or exome sequencing without prior clinical suspicion of Cornelia de Lange syndrome. In general, intractable epilepsy is not considered a prominent feature of Cornelia de Lange syndrome, yet this is found in these patients with SMC1A variants. Here we report on a series of patients with SMC1A variants and intractable epilepsy. In contrast to patients with typical SMC1A -associated Cornelia de Lange syndrome, all of the identified patients were female, and when available, X-inactivation studies were highly skewed with truncating variants. We describe the medical involvement and physical appearance of the participants, compared to the diagnostic criteria used for classical Cornelia de Lange syndrome. We also report on the clinical characteristics of the epilepsy, including age of onset, types of seizures, electroencephalographic (EEG) findings, and response to various antiepileptic medications. These findings allow us to draw conclusions about how this population of patients with SMC1A variants fit into the spectrum of Cornelia de Lange syndrome and the broader spectrum of cohesinopathies and allow generalizations that may impact clinical care and, in particular, epilepsy management.